WORKSHOP ON DEVELOPING CLASSROOM ACTION RESEARCH PROPOSALS BASED ON ARTIFICIAL INTELLIGENCE - Sulandra, I Made; Listiawan, Tomi; Azizah, Azizah; Agung, Mohammad; Meke, Konstantinus Denny Pareira; Masamah, Ulfah; Ariani, Wiga (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to implement Artificial Intelligence (AI) as a tool to assist teachers in developing Classroom Action Research (CAR) proposals. The use of AI has significant potential to support a more adaptive, systematic, and efficient proposal-writing process, reducing the time required. Through this technology, teachers are expected to more easily formulate research problems, develop background sections, and design instructional actions for use in the classroom. In addition, the use of AI is expected to enhance teachers’ confidence in conducting independent research and to promote continuous improvement in the quality of teaching and learning. The program is carried out through several stages, including a needs analysis to identify teachers’ challenges, workshops and mentoring sessions on AI-based CAR proposal development, and evaluation and reflection to assess outcomes and plan future improvements. Through this program, teachers are expected not only to understand the concept of Classroom Action Research but also to be able to develop effective proposals and utilize AI appropriately in their academic activities.